Cooperation Between China and Russia in the Field of Environmental Protection in the Arctic: Current State and Prospects - Fu Xinxin (Administrative Consulting, 2023)
In the Arctic, social, economic and environmental issues require the region’s countries to work together to preserve the planet and improve the well-being of people living in harsh conditions. The region is warming twice as fast as the global average, ice and snow are melting, ecosystems are transforming, and indigenous and local cultures are struggling to adapt to the new conditions. Thus, the engagement of key international actors such as Russia and China in Arctic sustainable development goals is more than a platform for international partnerships for caring about the planet and humanity. In view of the above situation, the author uses the method of comparative analysis and induction to discuss topical issues of Chinese-Russian cooperation in the field of environmental protection in the Arctic. Particular attention is paid to such areas of cooperation as the development of international environmental law and participation in working groups on various environmental aspects; satellite navigation in the Arctic region, joint research, expeditions and training, as well as exchange of research equipment and data. In addition, emphasis is placed on Russian-Chinese programs in the field of underwater observation and hydroacoustics.